MRD-driven phase 2 study of daratumumab, carfilzomib, lenalidomide, and dexamethasone in newly diagnosed multiple myeloma - Manisha Bhutani; Myra Robinson; David Foureau; Shebli Atrash; Barry Paul; Fei Guo; Jason M. Grayson; Anna Ivanina-Foureau; Mauricio Pineda-Roman; Cindy Varga; Reed Friend; Christopher J. Ferreri; et al. (Blood Advances)
Abstract: In newly diagnosed multiple myeloma (NDMM), measurable residual disease (MRD) status is prognostically important, but its role in treatment decisions remains unclear. In a phase 2 trial, we assessed daratumumab, carfilzomib, lenalidomide, and dexamethasone (Dara-KRd) induction followed by a next-generation sequencing–based MRD-adapted strategy. The primary outcome was complete response (CR) and stringent CR (≥CR) after induction. Flow cytometry was used to profile T cells. Among 39 patients, 21 (54%) achieved ≥CR after induction (P = .375), with MRD-negative rates of 59% (10−5) and 41% (10−6). Patients who were MRD-negative (n = 24, group A) received lenalidomide maintenance, showing sustained MRD negativity in 14 of 18 (77.8%) for ≥12 cycles. MRD-positive transplant-eligible patients (n = 8, group B) underwent autologous stem cell transplantation, with 62.5% converting to MRD-negative at 10−5 (37.5% at 10−6) posttransplant. MRD-positive, transplant-ineligible patients (n = 4, group C) received KRd consolidation. Best MRD-negative rates improved to 77% (10−5) and 72% (10−6). No new safety concerns were identified for Dara-KRd. With a median follow-up of 30.1 months, 3, 2, and 1 patient(s) in groups A, B, and C, respectively, have progressed or died. We observed that Dara-KRd strongly activated memory T cells, which was associated with an MRD-negative state post induction. Although the primary outcome was not met, Dara-KRd induction in NDMM achieved high ≥CR and MRD-negative rates without new safety concerns. The post induction MRD-adapted strategy deepened responses in MRD-positive patients and maintained durable MRD control in MRD-negative patients. This trial was registered at www.clinicaltrials.gov as #NCT04113018.